The Relationship Between Political and Security News on Iraqi Satellite Channels and Public Anxiety - Altimeemi, Median Umran; Mahmood, Mohammad Shakir (ALBAHITH ALALAMI, 2024)
This research aims to examine the relationship between political and security news broadcast on Iraqi satellite channels and the resulting feelings of anxiety among the public. The study was conducted on a sample of 426 individuals from the audience in Baghdad, selected using the multi-stage or cluster random sampling method. The research falls within the scope of "causal correlation studies" and utilizes a survey methodology, a questionnaire, and a measurement tool for data collection. The findings reveal that the public experiences a higher level of anxiety compared to the respondents when following political and security news on Iraqi satellite channels. This heightened anxiety is attributed to the chaotic political landscape, recurring disputes among political blocs, and the lack of control over consumer goods prices due to the instability of the dollar exchange rate. Additional contributing factors include the presence of armed manifestations within cities, the prevalence of crime and kidnapping, the widespread trade and abuse of drugs, and the absence of fundamental solutions to alleviate citizens’ suffering and provide for their basic needs. Furthermore, ongoing crises, such as strained relationships with neighboring countries, exacerbate feelings of intense anxiety and insecurity among citizens.